Hubungan antar pelaku usaha mikro kecil dan menengah di Pasar Kebalen Kota Malang pasca covid-19 - Brillianty, Farizah Auliya (Maliki Interdisciplinary Journal, 2024)
This article explores changes in cooperation, competition and support between MSME actors after the pandemic. This research uses a qualitative approach and data is collected through interviews and observation. The results show changes in the pattern of relationships between MSME actors, including increased cooperation and mutual support. This article provides important insight into the dynamics of relationships between MSME players in the Kebalen Market after the COVID-19 pandemic.